2019
DOI: 10.3389/fphar.2019.01022
|View full text |Cite
|
Sign up to set email alerts
|

N-3 Polyunsaturated Fatty Acids and the Resolution of Neuroinflammation

Abstract: In the past few decades, as a result of their anti-inflammatory properties, n-3 long chain polyunsaturated fatty acids (n-3 LC-PUFAs), have gained greater importance in the regulation of inflammation, especially in the central nervous system (in this case known as neuroinflammation). If sustained, neuroinflammation is a common denominator of neurological disorders, including Alzheimer’s disease and major depression, and of aging. Hence, limiting neuroinflammation is a real strategy for neuroinflammatory diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 237 publications
(369 reference statements)
1
68
0
Order By: Relevance
“…Recent evidence suggests that n-3 polyunsaturated fatty acids (PUFAs) exhibit anti-inflammatory activity through the synthesis of resolvins, protectins and maresins (bioactive mediators with pro-resolving properties). These mediators play a critical role in inflammation resolving [ 10 ]. In addition, PUFAs act on the cell membrane, providing a stabilizing effect and making it more resistant to damaging influences and more malleable for nerve impulse conduction [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that n-3 polyunsaturated fatty acids (PUFAs) exhibit anti-inflammatory activity through the synthesis of resolvins, protectins and maresins (bioactive mediators with pro-resolving properties). These mediators play a critical role in inflammation resolving [ 10 ]. In addition, PUFAs act on the cell membrane, providing a stabilizing effect and making it more resistant to damaging influences and more malleable for nerve impulse conduction [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that various ω-3/ω-6 PUFA diets are able to change the polarization of macrophages [7,8]. There is also evidence that ω-6and ω-3-derived oxylipins are able to modulate the inflammatory phenotype of immune cells, especially macrophages [7,9]. However, data on the changes in oxylipin profiles are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…SPM increases phagocytosis and suppresses inflammation by blocking the NF-κB pathway and PPAR-γ-mediated mechanism. According to lipid profiling, anti-inflammatory phenotype of microglia produces more quantity of protectins, maresin, and D-resolvins, whereas inflammatory phenotype of microglia produces more of ARA-derived proinflammatory markers [117,118]. Recently, the MaR1 pathway is found effective in the resolution phase.…”
Section: Lipid Mediators Drive Microglial Phenotypementioning
confidence: 99%